Using EHRs to advance epilepsy care. Issue 1 (February 2019) - Mbwana, Juma S.; Grinspan, Zachary M.; Bailey, Russell; Berl, Madison; Buchhalter, Jeffrey; Bumbut, Adrian; Danner, Zach; Glauser, Tracy; Glotstein, Angie; Goodkin, Howard; Jacobs, Brian; Jones, Lisa; et al.
Abstract : The improved use of Electronic Health Record (EHR) Systems provides an opportunity to improve the overall efficiency and quality of care of patients with epilepsy. Tools and strategies that may be incorporated into the use of EHRs include utilizing patient generated data, clinical decision support systems and natural language processing systems. Standardization of data from EHR systems may lead to improvement in clinical research through the creation of data collections and multi-center collaborations. Challenges to collaborative use of EHR Systems across centers include costs and the diversity of EHR systems.